The semiotic landscape and 3-year-olds' emerging understanding of multimodal communication practices. (June 2014) - Yamada-Rice, Dylan
This article considers the impact of the increasing use of the visual mode in texts found in urban landscapes on two 3-year-olds' understanding of communication practices. The data discussed are taken from a study into a group of 3- to 6-year-olds' interaction with and emerging comprehension of the visual mode and its connection to writing in multimodal texts. The research took place over a 6-month period in Japan. The data were collected using children's photographs of their interest in the visual mode, video recordings of environmental walks, interviews and mapping. They were analysed using content analysis, stop-motion animation and emerging themes. The data illustrates how the two 3-year-olds make meaning of the visual mode primarily through their knowledge of and interest in the physical world. It also shows how some of their visual mode comprehension is emerging through interest in fictional visual texts such as manga (Japanese comics), animation and digital games. It is hoped that the findings will initiate wider discourse in early childhood education around the importance of the visual mode to young children's comprehension of contemporary multimodal communication practices. This is important because the continuing development of digital media means the visual mode is increasingly foregrounded in multimodal communication practices.